2019
DOI: 10.1038/s41429-019-0164-1
|View full text |Cite
|
Sign up to set email alerts
|

New semisynthetic teicoplanin derivatives have comparable in vitro activity to that of oritavancin against clinical isolates of VRE

Abstract: Ten analogues of a teicoplanin pseudoaglycon derivative have been synthesized with the aim of optimizing the in vitro activity of the compound against VanA type vancomycin resistant enterococci (VRE) isolated from hospitalized patients. Teicoplanin, vancomycin and oritavancin were used as reference antibiotics for the antibacterial evaluations. One of the new derivatives exhibited far superior activity than the original compound. The in vitro MICs measured were comparable to that of oritavancin against the inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…[15][16][17] In recent years, we conducted a systematic study on the synthesis of lipophilic derivatives of the glycopeptide antibiotics vancomycin, teicoplanin and ristocetin, and this yielded several new antibiotics with promising antibacterial and antiviral activity. [18][19][20][21][22] We demonstrated that the high lipophilicity of the side chains (C 8 À C 10 alkyl groups) in these molecules is essential for antiviral activity against, among others, influenza virus. However, antiviral activity proved accompanied by high cytotoxicity, probably due to a membrane-disrupting effect of the highly lipophilic side chains.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] In recent years, we conducted a systematic study on the synthesis of lipophilic derivatives of the glycopeptide antibiotics vancomycin, teicoplanin and ristocetin, and this yielded several new antibiotics with promising antibacterial and antiviral activity. [18][19][20][21][22] We demonstrated that the high lipophilicity of the side chains (C 8 À C 10 alkyl groups) in these molecules is essential for antiviral activity against, among others, influenza virus. However, antiviral activity proved accompanied by high cytotoxicity, probably due to a membrane-disrupting effect of the highly lipophilic side chains.…”
Section: Introductionmentioning
confidence: 99%
“…The primary mechanism of action of GPAs is the binding to the d-Ala-d-Ala terminus of peptidoglycan precursors of bacterial cell wall, thus blocking mature cell wall assembly and, ultimately, leading to cell lysis [22,23]. In novel derivatives, the incorporation of a new membrane depolarization and disruption mechanism improves efficacy and evades resistance [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“… 161 Optimization of 23 led to compound 24 , characterized by the addition of a basic moiety at the C-terminus, which displayed improved activity against VanA-type VRE (MIC = 0.15–2.5 μg/mL) while retaining potency against MRSA (MIC = 0.3 μg/mL) and VanB-type VRE (MIC = 0.15 μg/mL) ( Table 1 ). 162 In another attempt to confer anti-VanA-type VRE activity to teicoplanin-like compounds, analogue 25 , bearing an N-terminal guanidine moiety, was also synthesized. 163 This led to a vast improvement in potency toward vanA VRE isolates, with most strains tested showing susceptibility (MIC = 0.1–1.6 μg/mL) and with only a few strains exhibiting higher MIC values (6.25–12.5 μg/mL).…”
Section: Recent Developments In Semisynthetic Glycopeptide Antibioticsmentioning
confidence: 99%